An improved active-front-end rectifier using model predictive control - Parvez M.; Mekhilef S.; Tan N.M.L.; Akagi H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Controllers; Cost functions; Efficiency; Electric inverters; Electric rectifiers; Frequency response; Model predictive control; Power electronics; Predictive control systems; Root loci; Ac-dc power conversion; Active front end rectifiers; Active front ends; Efficiency comparisons; Experimental system; Fast dynamic response; Frequency response technique; Stability analysis; Rectifying circuits